Pemanfaatan Cerita Rakyat Banten dalam Meningkatkan Keterampilan Membaca Siswa Sekolah Dasar - Yoma Hatima; Rina Yuliana (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to analyze the use of Bantenese folktales in improving elementary school students’ reading skills through a literature review approach. The focus of this study is on the utilization of folktales as part of local wisdom that contain educational, moral, and cultural values in Indonesian language learning. This research employs a literature review method by analyzing various relevant scientific sources, including journal articles, books, educational documents, and research studies related to folktales, reading literacy, and culture-based learning, particularly those published within the last ten years. The findings indicate that Bantenese folktales can enhance students’ reading interest due to their close connection with students’ social and cultural environments. In addition, folktales with simple plots, engaging characters, and easily understood moral messages are effective in improving students’ reading comprehension skills, especially in understanding text content and expanding vocabulary. Discussion and story interpretation activities also contribute to the development of students’ critical thinking skills. The integration of Bantenese folktales into classroom instruction not only improves reading skills but also strengthens students’ character formation, such as honesty, responsibility, cooperation, and appreciation of local culture. The main finding highlights that Bantenese folktales are more effective as contextual literacy media due to their cultural proximity to students compared to general reading materials. Teachers play an important role in selecting appropriate stories based on students’ developmental levels and implementing interactive learning strategies. Therefore, Bantenese folktales represent an effective, contextual, and culturally meaningful literacy learning medium that also supports the preservation of local culture in elementary education.